The mediating role of audit capacity stress in influencing factors of earnings management - Thendy Salim, Ega Erlinda; Louw, Febriana (International Enterprise Integration Association, 2025)
This study investigates the role that Audit Capacity Stress (ACS) plays as a mediator between different parameters and earnings management. The study focuses on 36 businesses that were listed between 2020 and 2022 on the Indonesia Stock Exchange (IDX) and included in the Kompas100 stock index. Purposive sampling was employed in a quantitative associative analysis method. Version 26 of the Statistical Package for the Social Sciences (SPSS) was used to analyze the data. The findings indicate that while Financial Distress (FD) has no discernible impact on Audit Capacity Stress (ACS), Audit Firm Reputation (AFR) and Audit Fee (AF) do. Earnings Management (EM) is also impacted by Audit Firm Reputation (AFR), Financial Distress (FD), Audit Fee (AF), and Audit Capacity Stress (ACS). While ACS does not mediate the relationship between Financial Distress (FD) and Earnings Management (EM), it does mediate the relationship between Audit Firm Reputation (AFR) and Audit Fee (AF) on Earnings Management (EM). This study provides information for more investigation into the elements influencing earnings management and the function of audit capacity stress.